Computation with photochromic memory - Chaplin, Jack Christopher (2013)
Unconventional computing is an area of research in which novel materials and paradigms are utilised to implement computation and data storage. This includes attempts to embed computation into biological systems, which could allow the observation and modification of living processes. This thesis explores the storage and computational capabilities of a biocompatible light-sensitive (photochromic) molecular switch (NitroBIPS) that has the potential to be embedded into both natural and synthetic biological systems. To achieve this, NitroBIPS was embedded in a (PDMS) polymer matrix and an optomechanical setup was built in order to expose the sample to optical stimulation and record fluorescent emission. NitroBIPS has two stable forms - one fluorescent and one non-fluorescent - and can be switched between the two via illumination with ultraviolet or visible light. By exposing NitroBIPS samples to specific stimulus pulse sequences and recording the intensity of fluorescence emission, data could be stored in registers and logic gates and circuits implemented. In addition, by moving the area of illumination, sub-regions of the sample could be addressed. This enabled parallel registers, Turing machine tapes and elementary cellular automata to be implemented. It has been demonstrated, therefore, that photochromic molecular memory can be used to implement conventional universal computation in an unconventional manner. Furthermore, because registers, Turing machine tapes, logic gates, logic circuits and elementary cellular automata all utilise the same samples and same hardware, it has been shown that photochromic computational devices can be dynamically repurposed. NitroBIPS and related molecules have been shown elsewhere to be capable of modifying many biological processes. This includes inhibiting protein binding, perturbing lipid membranes and binding to DNA in a manner that is dependent on the molecule's form. The implementation of universal computation demonstrated in this thesis could, therefore, be used in combination with these biological manipulations as key components within synthetic biology systems or in order to monitor and control natural biological processes.